2015
DOI: 10.1007/s12272-015-0559-x
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted factor peroxisome proliferator-activated receptor γ (PPARγ) in metabolism, immunity, and cancer

Abstract: The consumption of high-calorie foods combined with less physical exercise has increased the prevalence of obesity. Obesity is also associated with high blood pressure, atherosclerosis, insulin resistance, diabetes, impaired host defense, and the risk of some cancers. Because PPARγ is a central player that participates in various biological responses, including lipid metabolism, inflammation, and cell proliferation, further understanding of the lipid metabolic sensor PPARγ is necessary to reduce the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 114 publications
(110 reference statements)
0
37
0
2
Order By: Relevance
“…However, afar of its adipose functions PPARG is also vital for development of some important organs such as heart and the placenta [11]. Although most research on PPARG has been focused on its metabolic action, some of them are neurogenesis, osteogenesis, cancer, or cardiovascular disease [14]. Such pleiotropism of actions gives us a clue of the relevance of this transcription factor regarding health and disease.…”
Section: The Pparg Physiologymentioning
confidence: 99%
“…However, afar of its adipose functions PPARG is also vital for development of some important organs such as heart and the placenta [11]. Although most research on PPARG has been focused on its metabolic action, some of them are neurogenesis, osteogenesis, cancer, or cardiovascular disease [14]. Such pleiotropism of actions gives us a clue of the relevance of this transcription factor regarding health and disease.…”
Section: The Pparg Physiologymentioning
confidence: 99%
“…Pparγ is necessary and sufficient for adipogenesis [4]. Pparγ upstream regulators including CCAAT/enhancer binding protein (C/ebp), Early B cell factor, Interferon regulatory factor, Kruppel -like factor, early growth response, Inhibitor of DNA binding, Zinc finger proteins, and its downstream target genes have shown for their roles in lipid synthesis and adipocyte differentiation [5,6,7]. As Pparγ would be regulated by various integrated pathways, identification of a broader window of Pparγ upstream and its target genes linked to adipogenesis would provide further understanding of Pparγ and adipocyte biology.…”
Section: Introductionmentioning
confidence: 99%
“…AP is reported as a strong antioxidant that not only stifles the formation of ROS and free radical generation or augmentation of endogenous antioxidant enzymes but also modulates contractile function of heart and the survival or death signalling of ROS [36][37][38][39]. Flavonoids are also believed to play an important role in activation of PPARc which regulate the inflammatory response [40][41][42]. It is reported that PPARc may serve as a potential therapeutic target to prevent cardiac hypertrophy and heart failure in metabolic disorders [43,44].…”
Section: Introductionmentioning
confidence: 99%